A Clinical Case of Surgical Treatment of a Patient with Two Postinfarction Left Ventricular Aneurysms - Olena K. Gogayeva; Serhii A. Rudenko; Oleksandr O. Nudchenko; Svitlana V. Fedkiv (Ukrainian Journal of Cardiovascular Surgery, 2023)
Postinfarction left ventricular (LV) aneurysm develops as a result of untimely restoration of blood flow in the infarct-dependent artery and is associated with an increase in cardiac mortality. The presence of several postinfarction LV aneurysms of different localizations in one patient is a rare and casuistic case.Case description. Patient B., 53 years old, was urgently hospitalized in the National Amosov Institute with complaints of shortness of breath, pain behind the sternum with radiation to the left arm, occurring with minimal physical exertion. Electrocardiography showed scar changes in the anterior-apical-lateral area of the LV with a thrombosed aneurysm of the LV lateral wall. Echocardiography revealed a severe decrease in the global contractility of the LV with ejection fraction of 24% and aneurysms of the septal-apical and posterior-lateral segments of LV. Pericarditis was found, with a layer of fluid of 1.7 cm on the LV posterior wall and 2.0 cm on the LV apex. Emergency coronary angiography revealed an occlusion of the middle third of the left anterior descending artery and the middle third of the left circumflex coronary artery, 50-70% stenosis of the right coronary artery and confirmed widespread LV aneurysm. Cardiac magnetic resonance imaging with intravenous contrast confirmed the change in configuration and significant dilatation of the LV due to the formation of two LV aneurysms with mural thrombus in the cavity of the posterior-lateral LV aneurysm. After discussing the patient’s data, the cardiac team performed emergency on-pump coronary bypass surgery, resection of the LV aneurysm with thrombectomy. The operation took 5 hours, aorta cross-clamp time was 75 min, perfusion time was 117 min, intraoperative blood loss was 300 ml. The patient was extubated in 2 hours after the end of the operation, the length of intensive care unit stay was 2 days. On the 9th day after the operation, the patient was discharged from the Institute with positive clinical, electrocardiographic and echocardiographic (LV ejection fraction 38%) dynamics.Conclusions. This clinical case demonstrates successful surgical treatment of two LV aneurysms, a rare complication of acute myocardial infarction. Preoperative detailed diagnosis and discussion of the patient’s data by the heart team, selection of the optimal term and volume of the operation allowed to quickly stabilize the patient’s condition and achieve a positive immediate result.